HUBUNGAN PENGETAHUAN DAN KEPEMILIKAN JAMBAN TERHADAP KEJADIAN DIARE DI WILAYAH KERJA PUSKESMAS LAMPAHAN KABUPATEN BENER MERIAH TAHUN 2024 - Mardaleni; Magfirah, Afdhalul; Saipullah (Jurnal Ilmiah Cerebral Medika, 2025)
ABSTRACT The general objective of this study is to examine the relationship between knowledge and ownership of sanitation facilities with diarrhea incidence in the working area of UPTD Puskesmas Lampahan, Bener Meriah District, in 2024. This research is a quantitative analytical study with a cross-sectional approach. The study population consists of families experiencing diarrhea, totaling 118 respondents. The sample size is 91, selected using purposive sampling. The research instrument employed is a questionnaire. Univariate and bivariate analyses are conducted using the chi-square test. The results indicate that the average level of knowledge among respondents is sufficient, with 31 respondents (34.1%) having adequate knowledge. The number of households with sanitation facilities is 54 (59.3%), and those experiencing diarrhea is also 54 (59.3%). Based on the chi-square test results, the p-value for the knowledge variable is (0.001) ≥ (0.05), indicating that the alternative hypothesis (Ha) is accepted, and there is a relationship between knowledge and diarrhea incidence. For sanitation facility ownership, the p-value is (0.000) ≤ (0.05), meaning that the alternative hypothesis (Ha) is accepted, and there is a relationship between sanitation facility ownership and diarrhea incidence. It is recommended that the community enhance their understanding and awareness of the importance of environmental sanitation, including the ownership of sanitation facilities, as these are crucial in preventing disease vectors caused by feces. Keywords : Knowledge, Sanitation Facility Ownership, Diarrhea